Task representation and individual differences affect strategy selection and problem-solving performance - Xie, Xinyu; Moss, Jarrod (Frontiers in Psychology, 2025)
IntroductionWhile strategy selection theories generally posit that people will learn to prefer more successful task strategies, they often neglect to account for the impact of task representation on the strategies that are learned. The Represent-Construct-Choose-Learn (RCCL) theory posits a role for how changing task representations influence the generation of new strategies which in turn affects strategy choices. The goal of this study was to directly replicate and extend the results of one experiment that was conducted to assess the predictions of this theory.MethodsThe predictiveness of a feature of the task was manipulated along with the base rates of success of two task strategies in the Building Sticks Task. A sample of 144 participants completed this task and three individual differences tasks.ResultsThe results of the study replicated all prior results including: (1) a salient feature of the task influences people’s initial task representation, (2) people prefer strategies with higher base rates of success under a task representation, (3) people tend to drop features from the task representation that are found not to be useful, and (4) there are more representation and strategy changes when success rates are low. In addition to replication of these findings, individual differences in attentional control, working memory capacity, and inductive reasoning ability were measured and found to be related to BST problem-solving performance and strategy use. Critically, the effect of inductive reasoning and attentional control on solution time was found to be mediated by measures that tap into monitoring of problem attempts and more effective problem space exploration by avoiding repeating past attempts.DiscussionThe results support many of the predictions of RCCL, but they also highlight that other theories may better account for some details.